2005
DOI: 10.1242/jeb.01556
|View full text |Cite
|
Sign up to set email alerts
|

Body size, energy metabolism and lifespan

Abstract: Bigger animals live longer. The scaling exponent for the relationship between lifespan and body mass is between 0.15 and 0.3. Bigger animals also expend more energy, and the scaling exponent for the relationship of resting metabolic rate (RMR) to body mass lies somewhere between 0.66 and 0.8. Mass-specific RMR therefore scales with a corresponding exponent between -0.2 and -0.33. Because the exponents for mass-specific RMR are close to the exponents for lifespan, but have opposite signs, their product (the mas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

34
661
8
13

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 758 publications
(716 citation statements)
references
References 123 publications
34
661
8
13
Order By: Relevance
“…In our analysis, however, DEE and RMR were not significantly related to MLSP in birds after the effects of body mass and phylogeny were accounted for. These data are consistent with a previous analysis focussing primarily on mammals (Speakman 2005b), and highlight the critical importance of accounting adequately for size and phylogeny effects in comparative analyses (Promislow 1991;Speakman 2005a). One of the most important insights provided by Rubner was the observation that the product of lifespan and energy metabolism (based on RMR) was independent of body size.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…In our analysis, however, DEE and RMR were not significantly related to MLSP in birds after the effects of body mass and phylogeny were accounted for. These data are consistent with a previous analysis focussing primarily on mammals (Speakman 2005b), and highlight the critical importance of accounting adequately for size and phylogeny effects in comparative analyses (Promislow 1991;Speakman 2005a). One of the most important insights provided by Rubner was the observation that the product of lifespan and energy metabolism (based on RMR) was independent of body size.…”
Section: Discussionsupporting
confidence: 86%
“…Techniques such as the doubly labelled method are now available to quantify total daily energy expenditure (DEE) (Nagy 1983;Speakman 1998), and when these are used in comparative analyses rather than RMR, the supposed constancy of lifetime mass-specific energy expenditure in relation to body size disappears. In other words, when DEE is substituted for RMR data, our analyses have shown that smaller mammals actually burn more energy per gram of tissue during their lives than larger animals (Speakman 2005a).…”
Section: Introductionmentioning
confidence: 81%
“…Cabot’s terns have smaller body size and shorter life spans than the other investigated species [56, 98]. Body size is positively correlated with longevity, since small birds need to feed more frequently than large birds to fulfil their high metabolic rates [99, 100]. Furthermore, thermoregulation capacity is correlated with body size, making small-bodied species more vulnerable to low temperatures and the negative effect of oiling in the heat insulating properties of feathers [6, 101].…”
Section: Discussionmentioning
confidence: 99%
“…Across species, longevity is positively correlated with body mass (Haussmann et al., 2003; Lindstedt & Calder, 1976; Speakman, 2005). Generally, bird species live significantly longer than mammals of similar body size; however, understanding of the mechanisms that affect the increased longevity of birds is limited (Holmes and Austad, 1995a,b; Holmes, Fluckiger, & Austad, 2001).…”
Section: Introductionmentioning
confidence: 99%